The Hidden Struggles of Bangladeshi High School Students: Mental Health Crisis - Hassan Jubair (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aimed to assess the level of awareness and understanding of mental health among a purposefully selected sample of Bangladeshi high school students. We hypothesize that the population of Bangladeshi high school students has insufficient knowledge and comprehension about mental health, and this is a major reason behind the high burden of mental health problems in this group. In addition, parents are not aware of this topic and pay less attention to their children's mental health, and this shortage, coupled with the stigma, may further exacerbate the situation and less help-seeking behavior amongst students. The data was gathered through an online survey. Findings indicated a demand for greater attention to mental health education in high schools, to overcome cultural barriers and stereotypes to mental health concerns, and to emphasize parent education in mental health. Moreover, the research showed that a significant number of parents are not informed regarding mental health issues, and that could make the parents more vulnerable to their children's mental well-being. This work offers useful information regarding the present level of mental health awareness among Bangladeshi high school students and serves as an indication that research in this area will continue to be needed. Results hold promise for the design of culturally appropriate mental health interventions, designed to help increase mental health and reduce stigma within this community.